PREVALENCE, CLINICOTHERAPEUTIC AND PROPHYLACTIC STUDIES ON THEILERIOSIS IN DISTRICT SAHIWAL (PAKISTAN) - A. Qayyum; U. Farooq; H. A. Samad; H. R. Chauhdry (Journal of Animal and Plant Sciences, 2010)
A total of 300 exotic dairy cattle from various private livestock farms of district Sahiwal, Pakistan were selected to assess the incidence, effects on blood parameters, disease progression, therapeutic, and prophylactic aspects of tropical theileriosis. Animals were divided into two groups viz A and B. Group A (n=185) was kept as non-infected control whereas the group B (n=115) was diagnosed for theileriosis on clinical basis and further subdivided into two subgroups B1 (n=75): adult animals, and B2 (n=40): calves up to 1 year of age. The animals of group B (n=115 /38.33%) were treated with buparvaquone and long acting oxytetracyline at the dose rate of 2.5 and 20 mg/kg body weight intramuscularly, respectively and repeated at 48 hours interval. The same regimen was administered as a single dose to the healthy animals, prophylactically. The overall bi-monthly incidence rate recorded in April-May, June-July and August-September was 31.0, 59.0 and 25.0%, respectively. Group B1 accounted for 61.54% of the disease with the highest frequency during June-July The overall case fatality rate was 18.26% being significantly higher during months of June-July (22.03%) Hematological parameters showed a significant decrease in the mean values of hemoglobin concentration, Packed Cellular Volume (PCV), Total Erythrocyte Count (TEC), and Total Leukocyte Count (TLC) in comparison to those of healthy animals. Therapeutic and prophylactic efficacy of Buparvaquone and oxytetracycline was 81.73 and 100%, respectively. The recovery rates for group B1 and B2 were 81.33 and 82.50%, respectively. It may be concluded that bupaquone and long acting oxytetracycline in combination are quite effective both for treatment and prevention of disease
Keywords: Theileriosis; buparvaquone; hematology; cross-breeding; case fatality